2013
DOI: 10.4236/ajps.2013.43083
|View full text |Cite
|
Sign up to set email alerts
|

The Sucrose Starvation Signal Mediates Induction of Autophagy- and Amino Acid Catabolism-Related Genes in Cowpea Seedling

Abstract: In higher plants, autophagy is bulk degradation process in vacuole necessary for survival under nutrient-limited conditions and plays important roles in senescence, development and pathogenic response, etc. Cowpea is one of the most important legume crops in semi-aride region, which is highly tolerant to drought stress. Changes of photoassimilate status by drought stress and/or sink-source balance appeared to affect autophagy and senescence of leaf in cowpea. Accordingly, we focused on roles of sucrose signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…A phylogenic analysis of deduced amino acid sequences of bZIP53 homologs of Arabidopsis thaliana, soybean (Glycine max (L.) Merr. ), and cowpea (Vigna unguiculata L.) showed that GmbZIP53A, GmbZIP53B, and VubZIP53 (accession number AB77966) are classified into one clade containing bZIP1 and bZIP53 (Figure 1(a)) [17].…”
Section: Genementioning
confidence: 99%
“…A phylogenic analysis of deduced amino acid sequences of bZIP53 homologs of Arabidopsis thaliana, soybean (Glycine max (L.) Merr. ), and cowpea (Vigna unguiculata L.) showed that GmbZIP53A, GmbZIP53B, and VubZIP53 (accession number AB77966) are classified into one clade containing bZIP1 and bZIP53 (Figure 1(a)) [17].…”
Section: Genementioning
confidence: 99%